Espaços de existência: identidade, poesia e emancipação em um sarau periférico - Gunutzmann, Pricila (2017)
This thesis sought to investigate the identity metamorphosis and their senses from the life story narratives of some of the participants of the “Sarau do Binho”. For this, we started from Social Psychology, having as central category the identity, seen from the syntagm identity-metamorphosis-emancipation (CIAMPA, 2009), seeking to understand the phenomenon in a social political context. Through the analysis of the life stories of five participants of the “Sarau do Binho”, we understand the processes of transformation and the possibility of emancipatory fragments that exist in and through the space in which the main force is art. When analazing the story of “Sarau do Binho” we understand the differentials that constitute this space of sociability, in which art, in this space understood by us as Dionysiac (NIETZSCHE, 1999), presents itself. The Sarau is a place of sharing and artistic production with projects that spread art through the city of Sao Paulo. Our thesis is that the “Sarau do Binho” is a space of sociability where Dionysian art is an enabler of new ways of existing, thus providing metamorphoses and new characters (individual and collective ones) that integrate new identities. It is a space of believable utopia. Our analysis point to identity policies, political identities and the construction and appreciation of collective characters. In this way, this work has reflections and considerations on a certain peripheral sarau that has enabled new modes of existance and fragments of emancipation through an art that doesn´t exempt its Dionysiac elements, such as experience, confrontation of opposing passions and festivity